Popularização da ciência : o ensino de física em comunidades rurais - Machado, Fernando Oliveira (2019)
The popularization of science is a reflexive and communicative cultural action that seeks to spread science among people who have little access to scientific and technological knowledge. This work presents an investigation carried out with residents of a rural community in which an action to popularize science was carried out. The investigation started from the following question: How does an action to popularize science, specifically focused on the knowledge of Physics, contribute to scientifically clarify everyday facts in a rural community? The theoretical bases of this work were based on the concepts of popularization of science, non-formal spaces of education and on David Ausubel's theory of significant learning. With the intention of sharing scientific and technological knowledge with residents of a rural community, this work presents the elaboration, implementation and analysis of an action to popularize science in the format of three pedagogical workshops. For this, at first, an exploratory research was carried out in a quilombola rural community, in the city of Caçapava do Sul, on the concepts of its residents on the themes: work safety, health and communication. From this, a didactic proposal was constructed in the format of three workshops in which everyday situations of this community were approached, observing the themes previously chosen. The data, obtained from the dialogues between the participants and the researcher, during the workshops, were gathered through audio recordings, transcribed in full and analyzed according to the assumptions of the Discursive Textual Analysis. This work of popularizing science proved to be able to contribute to scientifically clarifying everyday facts of residents of the participating rural community. The results of the research on the participation of residents in the proposed activities and the dialogue carried out with the researcher registered the occurrence of changes in habits and a better understanding of the role of science and technology in their daily actions. The educational product of this dissertation is an e-book, disseminable among educators and interested in the popularization of science.